Conservative Management of Major Liver Necrosis after Angioembolization in a Patient with Blunt Trauma - Husham Abdelrahman; Ahmad Ajaj; Sajid Atique; Ayman El-Menyar; Hassan Al-Thani (Case Reports in Surgery)
Management of liver injury is challenging particularly for the advanced grades. Increased utility of nonoperative management strategies increases the risk of developing massive liver necrosis (MLN). We reported a case of a 19-year-old male who presented with a history of motor vehicle crash. Abdominal computerized tomography (CT) scan revealed large liver laceration (Grade 4) with blush and moderate free hemoperitoneum in 3 quadrants. Patient was managed nonoperatively by angioembolization. Two anomalies in hepatic arteries origin were reported and both vessels were selectively cannulated and bilateral gel foam embolization was achieved successfully. The patient developed MLN which was successfully treated conservatively. The follow-up CT showed progressive resolution of necrotic areas with fluid replacement and showed remarkable regeneration of liver tissues. We assume that patients with high-grade liver injuries could be managed successfully with a carefully designed protocol. Special attention should be given to the potential major associated complications. A tailored multidisciplinary approach to manage the subsequent complications would represent the best recommended strategy for favorable outcomes.